Graphene nano-sieves by femtosecond laser irradiation. (5th March 2023) - Katsiaounis, S; Chourdakis, N; Michail, E; Fakis, M; Polyzos, I; Parthenios, J; Papagelis, K
Abstract: The formation of nano-pores in graphene crystal structure is alternative way to engineer its electronic properties, chemical reactivity, and surface interactions, enabling applications in technological fields such as sensing, energy and separation. The past few years, nano-perforation of graphene sheets has been accomplished by a variety of different methods suffering mainly from poor scalability and cost efficiency issues. In this work, we introduce an experimental protocol to engineer nanometer scale pores in CVD graphene membranes under ambient conditions, using low power ultra-short laser pulses and overcoming the drawbacks of other perforation techniques. Using Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM) we visualized and quantified the nanopore network while Raman spectroscopy is utilized to correlate the nano-perforated area with the nanotopographic imaging. We suggest that Raman imaging provides the identification of nanoporous area and, in combination with AFM, we provide solid evidence for the reproducibility of the method, since under these experimental conditions, nanopores of a certain size distribution are formed.